The Role of Digital Marketing on the Performance of Cut Flower Export Businesses in Tanzania: A Case Study of Arumeru District, Arusha - Julius , Editha (PERFECT EDUCATION FAIRY, 2025)
This study aims to analyze the impact of digital marketing on the performance of cut flower export businesses in Arumeru District, Arusha, Tanzania. The primary focus is on the adoption rate of digital marketing, perceived usefulness and ease of use of digital technologies, and the factors influencing digital marketing adoption decisions among cut flower exporters. A Systematic Literature Review (SLR) approach was employed to synthesize relevant theoretical and empirical findings. The review indicates that variables such as gender, education level, social media presence, digital advertising, access to credit, the role of Non-Governmental Organizations (NGOs), and business location significantly influence digital marketing adoption. A practical implication of these findings is the necessity for enhancing human resource capacity through continuous digital marketing training. This study contributes to the literature on the digital economy and technology-based export development policies within the agribusiness sector.